2015
DOI: 10.1159/000377634
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Kidney Programming by Maternal Smoking Exposure: Effects on Kidney Structure, Blood Pressure and Urinary Sodium Excretion in Adult Offspring

Abstract: Introduction: Fetal programming by different insults results in low birth weight and reduction in nephron number increasing the risk for adult development of cardiovascular and renal diseases. Maternal smoking is an important modifiable adverse fetal exposure worldwide and leads to a decrease in the offspring's birth weight. Thus far, the specific adverse fetal smoking exposures and mechanisms underlying these associations on renal development and functional disorder are unclear. Methods: The present study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…Mothers who smoke tobacco during pregnancy can permanently damage their offspring’s kidney health as a result of prematurity and low birth weight [ 64 , 65 ]. This is due to the disruption in delivery of nutrients to the growing fetus that leads to intrauterine growth restriction, which has permanent deleterious effects on renal health in postnatal life [ 66 ]. Though often associated with fetal overgrowth, maternal obesity can also conversely be associated with increased risk of premature birth and low birth weight, with implications for renal development and CKD risk [ 67 ].…”
Section: Developmental Programming Of Kidney Disease In Offspringmentioning
confidence: 99%
“…Mothers who smoke tobacco during pregnancy can permanently damage their offspring’s kidney health as a result of prematurity and low birth weight [ 64 , 65 ]. This is due to the disruption in delivery of nutrients to the growing fetus that leads to intrauterine growth restriction, which has permanent deleterious effects on renal health in postnatal life [ 66 ]. Though often associated with fetal overgrowth, maternal obesity can also conversely be associated with increased risk of premature birth and low birth weight, with implications for renal development and CKD risk [ 67 ].…”
Section: Developmental Programming Of Kidney Disease In Offspringmentioning
confidence: 99%
“…These findings were associated with evidence of increased oxidative stress and changes in mitochondrial structure and function in offspring kidneys [350]. Similarly, in rats exposed to maternal smoking, birth weights and nephron numbers were reduced, proinflammatory proteins were upregulated in offspring kidneys, and albuminuria and blood pressure increased over time [111,351]. A prospective cohort study found that exposure to maternal smoking during pregnancy was associated with a dose-dependent reduction in fetal and infant kidney volumes after adjustment for multiple variables, suggesting an independent impact of smoking on fetal kidney development [114,352].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Indeed, the Barker hypothesis sprung from the observation that lower birthweight infants were more likely to develop later life hypertension (Barker et al, 1989). While several mechanisms of developmentally programmed hypertension and renal disease have been proposed (Baum, 2010; Block et al, 2015; Schreuder and Nauta, 2007), a consensus document by the Low Birth Weight and Nephron Number working group highlighted “the need to act early to prevent CKD and other related noncommunicable diseases later in life by reducing low birth weight, small for gestational age, prematurity, and low nephron numbers at birth through coordinated interventions” (Low Birth and Nephron Number Working, 2017).…”
Section: Discussionmentioning
confidence: 99%